2011
DOI: 10.4028/www.scientific.net/kem.462-463.213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on Compressive Behaviour of Aluminium Honeycomb and Titanium Alloy Micro Lattice Blocks

Abstract: The paper discusses the compressive behaviour of two materials, the conventional aluminium honeycomb and the new titanium alloy micro lattice blocks. The new titanium alloy micro lattice structure is being developed as core material candidate in sandwich construction for aerospace application. Experimental tests have been done on the blocks in order to compare its property with the aluminium honeycomb. Compression strength as well as compressive behaviour of both materials are compared and observed. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…All curves, in every heat treatment condition, are characterized by an initial linear elastic growth up to a stress maximum, followed by a decrease in stress due to shear deformation; thereafter some low-stress oscillations take place. No plateau-like region was present in the studied conditions, as could be expected considering the selected geometry of the unit cell, [29,30] This behavior, as evidenced by the samples photographs shown in Figure 6, is connected to the progressive bending and collapse of struts belonging to shear planes, which lie at 45 with respect to the loading direction. In particular, the first large stress peak is related to the formation of an extensive shear band encompassing the whole sample, whereas successive reduced oscillations are connected to smaller shear bands, which comprise a lower number of unit cells.…”
Section: Microstructural and Mechanical Characterizationsupporting
confidence: 65%
“…All curves, in every heat treatment condition, are characterized by an initial linear elastic growth up to a stress maximum, followed by a decrease in stress due to shear deformation; thereafter some low-stress oscillations take place. No plateau-like region was present in the studied conditions, as could be expected considering the selected geometry of the unit cell, [29,30] This behavior, as evidenced by the samples photographs shown in Figure 6, is connected to the progressive bending and collapse of struts belonging to shear planes, which lie at 45 with respect to the loading direction. In particular, the first large stress peak is related to the formation of an extensive shear band encompassing the whole sample, whereas successive reduced oscillations are connected to smaller shear bands, which comprise a lower number of unit cells.…”
Section: Microstructural and Mechanical Characterizationsupporting
confidence: 65%
“…Studies on SLM Ti6Al4V micro-lattice structure as core material in sandwich construction showed that this material has significant potential that merits further examination and analysis [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…The potential of the SLM Ti6Al4V material as high performance parts in aerospace, automotive and medical applications is actively being explored by researchers and companies throughout the world. Studies on SLM Ti6Al4V micro-lattice structure as core material in sandwich construction showed that this material has significant potential that merits further examination and analysis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In compression test, stress and strain are the important elements to plot the graph to determine the ultimate strength, yield strength, elastic limit and for some material's compressive strength. Numerous studies have utilized compression test to measure the strength [7,11]. Ang et al [12] studied the effect of fused deposition modelling (FDM) process parameters to the mechanical strength of tissue engineering scaffold by compression test.…”
Section: Introductionmentioning
confidence: 99%